Where do Australian children get their dietary fibre? A focus on breakfast food choices. Issue 2 (26th September 2012) - Grieger, Jessica Anne; Kim, Susan; Cobiac, Lynne
Abstract: Aims:  There is little data in Australian children assessing dietary fibre intakes or ready‐to‐eat cereal consumption. The aims were to: (i) assess the dietary fibre intake of 2‐ to 16‐year‐old children from the 2007 Australian National Children's Nutrition and Physical Activity Survey; (ii) determine the percentage of children meeting adequate fibre intake; and (iii) determine the contribution of breakfast and ready‐to‐eat cereal fibre intake. Methods:  Secondary analysis of the 2007 Australian National Children's Nutrition and Physical Activity Survey. Results:  On the day of the survey, the mean (SE) dietary fibre intake among all children at breakfast was 4.5 (0.1) g and total daily fibre intake was 20.7 (0.2) g. Fibre adequacy was achieved by 50% of Australian children. Forty‐nine percent of all children consumed ready‐to‐eat cereal, providing 2/3 of fibre intake at breakfast and 1/10 of total daily fibre intake. Consuming ready‐to‐eat cereal was a significant predictor of total daily fibre intake (β= 0.028). Over 60% of all children consumed ready‐to‐eat cereal in which at least a 'source' of fibre (1.5–3.0 g) was available; however, <10% of children consumed ready‐to‐eat cereal containing a 'very high source' of fibre (≥6.0 g). Conclusions:  While ready‐to‐eat cereal was only consumed by close to half of all children, it was a significant contributor of fibre at both the breakfast meal occasion and over the whole day. Randomised controlled trials are necessary to identify whether increasing consumption of fibre from ready‐to‐eat cereal alters health outcomes such as anthropometric and biochemical end points.